2018
DOI: 10.1177/1081286518757299
|View full text |Cite
|
Sign up to set email alerts
|

Decay of solutions for a one-dimensional porous elasticity system with memory: the case of non-equal wave speeds

Abstract: In previous work, Apalara considered a one-dimensional porous elasticity system with memory and established a general decay of energy for the system in the case of equal-speed wave propagations. In this paper, we extend the result to the case of non-equal wave speeds, which is more realistic from the physics point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…piecewise constant) memory kernel. For more papers related to the Timoshenko beam with memory, we refer the reader to the works of Ammar-Khodja et al [21], Feng and Yin [22], Guesmia and colleagues [23][24][25], Muñoz Rivera and Fernández Sare [26] and references therein. It is worth mentioning that there is no result concerning a laminated beam with structural damping and infinite memory.…”
Section: Introductionmentioning
confidence: 99%
“…piecewise constant) memory kernel. For more papers related to the Timoshenko beam with memory, we refer the reader to the works of Ammar-Khodja et al [21], Feng and Yin [22], Guesmia and colleagues [23][24][25], Muñoz Rivera and Fernández Sare [26] and references therein. It is worth mentioning that there is no result concerning a laminated beam with structural damping and infinite memory.…”
Section: Introductionmentioning
confidence: 99%
“…There, the author showed that generically the porous dissipation is not strong enough to guarantee the exponential decay of the solutions for a porous elastic structure. From this contribution a big quantity of contributions have been developed to clarify the decay of the thermomechanical perturbations for elastic solids with voids when dierent eects are taken into account [1,3,10,11,18,21,27,29,30,33]. It is accepted that generically we would need two dissipative mechanisms to guarantee the exponential decay of solutions.…”
Section: Introductionmentioning
confidence: 99%
“…By assuming g (t) ≤ −η(t)g(t), the author established a general decay result in the case of the equal-speed wave propagation case under the assumption that the constant b is positive. Recently, the present author and his co-author, Feng and Yin [11], extended the result to the case of the non-equal wave speeds, and the result also holds for b < 0. For more results concerning the stability to porous elastic solids, one can refer to [12,23,26,29,30,31] and so on.…”
mentioning
confidence: 57%